Weight loss is associated with improvements in cognitive function among overweight and obese people: A systematic review and meta-analysis. (January 2017) - Veronese, Nicola; Facchini, Silvia; Stubbs, Brendon; Luchini, Claudio; Solmi, Marco; Manzato, Enzo; Sergi, Giuseppe; Maggi, Stefania; Cosco, Theodore; Fontana, Luigi
Highlights: In our meta-analysis, weight loss was associated with an improvement in attention and memory. Executive function and language improved in longitudinal and RCT studies, respectively. Intentional weight loss should be promoted in obese/overweight people. Abstract: Whilst obesity is associated with a higher risk of cognitive impairment, the influence of weight loss on cognitive function in obese/overweight people is equivocal. We conducted a meta-analysis of randomized controlled trials (RCTs) and longitudinal studies evaluating the influence of voluntary weight loss on cognitive function in obese/overweight individuals. Articles were acquired from a systematic search of major databases from inception till 01/2016. A random effect meta-analysis of weight loss interventions (diet, physical activity, bariatric surgery) on different cognitive domains (memory, attention, executive functions, language and motor speed) was conducted. Twenty studies (13 longitudinal studies = 551 participants; 7 RCTs = 328 treated vs. 140 controls) were included. Weight loss was associated with a significant improvement in attention and memory in both longitudinal studies and RCTs, whereas executive function and language improved in longitudinal and RCT studies, respectively. In conclusion, intentional weight loss in obese/overweight people is associated with improvements in performance across various cognitive domains. Future adequately powered RCTs are required to confirm/refute these findings.